Genealogi Hukum Ekonomi Islam Bottom-Up: Dari Praktik Perdua dan Jual Janji ke Skema Pembiayaan BRK Syariah - Bobby Ferly; Asasriwarni Asasriwarni; Ikhwan Ikhwan; Salma Salma; Elfia Elfia (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The discourse of Islamic economic law in Indonesia often highlights the tension between a textualist (top-down) approach and a sociological reality (bottom-up). This study traces the genealogy of Islamic economic law in Riau Province through a bottom-up approach, with a focus on the full conversion of PT Bank Riau Kepri (BRK) into an Islamic bank. This conversion was driven by regional policies and Malay-Islamic cultural identity based on the principle of